Feeding During Infancy: Interpersonal Behavior, Physiology, and Obesity Risk. (14th July 2020) - Hodges, Eric A.; Propper, Cathi B.; Estrem, Hayley; Schultz, Michael B.
Abstract: Infancy is a sensitive developmental period that presents both opportunities and challenges for caregivers to feed their infants in ways that support healthy growth and development. The capacity to eat in a way that supports energy (caloric) intake aligned with the body's physiologic need for growth and development appear to diminish in the years following infancy, but the reasons for this and whether this is developmentally typical are unclear. Feeding interactions that undermine infants' ability to regulate their intake in response to hunger and satiety are thought to confer risk for obesity in infancy and beyond. In this integrative review, we consider what we know about the emergence of self‐regulation of behavior and emotion from both a behavioral and a physiological perspective. Then, we apply this information to our emerging understanding of how self‐regulation of energy intake may be derailed through feeding interactions between caregivers and infants.